2013
DOI: 10.1111/cns.12155
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination Initiated by Oligodendrocyte Apoptosis through Enhancing Endoplasmic Reticulum–Mitochondria Interactions and Id2 Expression after Compressed Spinal Cord Injury in Rats

Abstract: Demyelination occurred after CSCI and might be partly caused by oligodendrocyte apoptosis, which was positively correlated with ER-mitochondria interactions and enhanced Id2 expression after CSCI in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 85 publications
1
29
0
Order By: Relevance
“…In addition to these changes, layers of the myelin sheath were folded, wrinkled, and disorganized, with evidence of demyelinated areas seven days after CSCI. Similarly, other authors [30] found that myelin sheaths became swollen, degenerated and were broken down gradually. In addition, the axolemma was separated from the myelin sheath.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition to these changes, layers of the myelin sheath were folded, wrinkled, and disorganized, with evidence of demyelinated areas seven days after CSCI. Similarly, other authors [30] found that myelin sheaths became swollen, degenerated and were broken down gradually. In addition, the axolemma was separated from the myelin sheath.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, the axolemma was separated from the myelin sheath. The axoplasm in the lesion area contained varying degrees of reduction in the mitochondria and microtubules [30].…”
Section: Discussionmentioning
confidence: 99%
“…ER is responsible for lipid synthesis, protein folding, protein synthesis and intracellular calcium homeostasis. Additionally, there is increasing evidence that ER plays a significant role in the regulation of cell apoptosis, which depends on the intrinsic mitochondria‐mediated death signaling pathway . ER stress induces the expressions of GRP78 and CHOP, which are the ER stress‐related apoptotic factor, and stimulates the unfolded protein response that is closely related with mitochondrial dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the sections were immersed in 1% cresyl violet solution for 10 min and quickly dehydrated with 70% and 95% alcohol until myelinated tracts of the spinal columns were stained blue [27]. Three sections per mice were chosen for assessing the myelinated area of spinal white matter.…”
Section: Methodsmentioning
confidence: 99%